Overview of Artificial Intelligence in Justice and Law today - Lacruz Mantecón, Miguel L. (Revista de derecho aragonés, 2024)
The article attempts to make a sufficiently complete summary of the issue of the impact of the new technology of Artificial Intelligence in the legal field. To do this, we start from Spanish and European legislation in this area, which is broad enough to provide enough data about current developments and possible future directions. The achievements and forecasts regarding this technology are examined in relation to the different legal 98 RDA-2024 - XXX specializations, and they are attempted to be completed with examples that I hope are sufficiently illustrative.